SEM, EBSD, laser confocal microscopy and FE-SEM data from modern Glycymeris shell layers - Crippa, Gaia (Data Brief, 2020)
Here, we provide the dataset associated with the research article “Orientation patterns of aragonitic crossed-lamellar, fibrous prismatic and myostracal microstructures of modern Glycymeris shells” [1]. Based on several tools (SEM, EBSD, laser confocal microscopy and FE-SEM) we present original data relative to the microstructure and texture of aragonite crystallites in all Glycymeris shell layers (crossed-lamellar, complex crossed-lamellar, fibrous prismatic and pedal retractor and adductor myostraca) and address texture characteristics at the transition from one layer to the other, identifying similarities and differences among the different layers. Shells were cut transversely, obliquely and longitudinally in order to obtain different orientated sections of the outer and inner layer and of the myostraca. The identification of major microstructural elements was provided by detailed SEM and laser confocal microscopy images. Microstructure and texture characterization was based on EBSD measurements presented as band contrast images and as color-coded crystal orientation maps with corresponding pole figures. Crystal co-orientation was measured with the MUD value. Finally, the distribution of the organic matrix occluded within the outer crossed-lamellar layer was revealed using FE-SEM. These data, besides providing a modern unaltered Glycymeris reference to detect diagenetic alteration in fossil analogs used for paleoenvironmental reconstructions, are useful to better comprehend the mechanisms of bivalve shell formation.